Exploring AI Literacy and Perception: Insights from Iranian EFL Researchers - Asghar Moulavinafchi (Journal of Modern Research in English Language Studies)
The rapid integration of Artificial Intelligence (AI) into education has transformed teaching and research practices, particularly in the context of English as a Foreign Language (EFL). However, the effective adoption of AI in EFL research requires a deep understanding of AI literacy and stakeholder perceptions. This mixed-methods study investigates Iranian EFL researchers' AI literacy, perceptions of AI applications, and their implications for research and pedagogy. Quantitative data were collected through a validated AI Literacy Questionnaire administered to 112 participants, measuring nine dimensions of AI literacy, including technical skills, ethical considerations, and emotional regulation. Results revealed low AI literacy levels across all dimensions, with significant gaps in advanced skills like AI creation and ethical analysis. Cluster analysis identified three proficiency groups: high, moderate, and low, with the majority falling into the low proficiency category. Qualitative data from semi-structured interviews with 16 participants highlighted both positive and negative perceptions of AI in research. While participants acknowledged AI's potential for enhancing data analysis, time efficiency, and writing accuracy, concerns included ethical risks, data privacy issues, and overreliance on AI, which could stifle creativity and critical thinking. These findings underline the pressing need for targeted training programs and policy interventions to enhance AI literacy among Iranian EFL researchers, fostering responsible and effective AI integration in research and education.